Implementasi Metode AHP dan Multi-Objective Optimization by Ratio (MOORA) dalam Pemilihan Motor Listrik - Sembiring, Kristian Eykman; Purnomo, A Sidiq (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2024)
The mode of transportation is very widely used because it is an access to take one place to another and is also used as a tool to transport an object. There are many types of transportation in Indonesia, one of which is a motorcycle. The increasing number of motorcycle users who consume fuel oil (BBM), raises concerns about climate change and air pollution. With these concerns, it can increase public awareness of the importance of protecting the environment. Efforts can be made to protect the environment in using transportation equipment, namely by using fuel from electrical energy. The number of electric motorbikes on the market with various types, makes it difficult for ordinary people to determine the choice of electric motorbikes that match their wishes and on average ordinary people determine the choice of motorbikes only from brands, selling prices, and do not understand the specifications of each of the criteria on electric motorbikes. From this problem, the researcher presents a decision support system to support lay people in determining the desired electric motorbike, using the AHP method to determine the weight and continued with the MOORA method to get the recommended electric motorbike. Electric motors that have affordable prices with good specifications get the highest rank in ranking with a value of 0.0718. The purpose of this research is to increase understanding of the factors that are important in the selection of electric motors, this method has never been used before for the selection of electric motors so it is hoped that the results of this research can develop new methods for selecting electric motors, and this research can provide recommendations for the best electric motors for prospective buyers so as to facilitate prospective buyers in making decisions in selecting electric motors.